Análise de cascas de revolução pelo método dos elementos finitos com elemento de casca axissimétrico - Galeão, Augusto Cesar Noronha Rodrigues (1973)
The static linear analysis of axi-symmetric shells under axially symmetric loading is done by the finite element method. For this purpose a truncated cone element is used to take advantage of the symmetry or the structure. Three interior degrees of freedom are introduced for each element, resulting in improved displacement functions. The effect of stiffness rings is taken into account. A circular plate element with one node, is used to handle the singularities with appear when dealing with closed shells. A computer program based on the cone element was prepared. Some examples are solved using the program and the results are compared with those of available analytical solutions.